THE INFLUENCE OF BRAND IMAGE, PRICE, AND PRODUCT QUALITY ON PURCHASE DECISIONS OF SKINTIFIC PRODUCTS IN DENPASAR - Ni Komang Sri Juniastrini; Made Mulyadi (Sekolah tinggi ilmu ekonomi pemuda, 2026)
The skincare industry in Indonesia has shown rapid growth along with increasing awareness of skin healthand the influence of digital marketing. Skintific, a science-based skincare brand, has gained significantpopularity among young consumers in Denpasar. This study aims to examine the influence of brand image,price, and product quality on consumer purchase decisions. Using a quantitative associative method, 160 respondents were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The results show that brand image, price,and product quality significantly influence purchase decisions both partially and simultaneously. Product quality is the most dominant factor affecting consumer decisions. The coefficient of determination (R²) indicates that 68.4% of purchase decisions are influenced by these variables. This study highlights the importance of strengthening brand image, maintaining competitive pricing, and improving product quality to enhance consumer purchasing decisions. Keywords: Brand Image, Price, Product Quality, Purchase Decision, Skincare, Skintific.